ANALISIS TEBAL PERKERASAN RUNWAY PADA BANDARA INTERNASIONAL OE-CUSSE, TIMOR LESTE - Sahat Martua Sihombing; Achmad Pahrul Rodji; Al Muzamil (Jurnal Sipil Krisna, 2022)
Oecusse-Ambeno is one of the districts in Timor Leste which is being developed by the government. Oneof the developments is through the implementation of an airport project called the "New Development of OecusseInternational Airport Project" which aims to increase access to Timor Leste and as an exclusive economicdevelopment zone for Timor Leste. Over time, the level of runway pavement can decrease. Therefore, the qualityof the pavement structure must be considered so that it is able to serve the planned traffic over the coming period.The author uses the standard rules of the Federation Aviation Administration (FAA) as the basis for planning theair side of the airport. This air side planning, adjusts to passenger growth for the next 20 years. Airside geometricrequirements are runway length 2200 m with a width of 45 m. In this analysis using the auxiliary program, namelythe manual method and FAARFIELD. Based on the results of calculations using FAARFIELD software andgraphics, the type of aircraft planned for the A330-330 within the next 20 years development period is the totalpavement thickness with FAARFIELD software is 658 mm, which consists of 120 mm surface course, 343 mmBase Course, and 195 mm Subbase Course while the graphical method obtained a total pavement thickness of730 mm, consisting of 102 mm Surface Course, 480 cm Base Course, and 152 mm Subbase Course. The differencein the calculation of the FAARFIELD software by graphical method is 10% or the difference is about 72 mm, sothe results of the calculation of the graphical method are thicker than FAARFIELD.